Suppression of multiple processes relevant to cancer progression by benzyl isothiocyanate may result from the inhibition of Aurora A kinase activity. Issue 10 (5th October 2020) - Yu, Tzu-Tung; Chang, Meng-Ya; Hsieh, Yi-Jen; Chang, Chih-Jui
Abstract : The anti-cancer properties of BITC may result from the inhibition of Aurora A kinase activity. Abstract : Cruciferous vegetables are good sources of phytochemicals that have the potential to prevent cancer. Benzyl isothiocyanate (BITC) is the hydrolysis product of glucosinolates that are especially abundant in cruciferous vegetables. The anti-cancer activities of BITC have been studied for decades. The mechanisms of reducing the incidence of cancer by BITC involve multiple pathways, including the inhibition of proliferation, induction of apoptosis and inhibition of angiogenesis. One of the major common phenotypes induced by BITC in previous studies is G2/M cell cycle arrest. Therefore, interference of mitosis progression is likely to be an important anti-tumor mechanism of BITC. Using immunofluorescence staining, we show that BITC induces cell arrest in mitosis by perturbation of mitotic spindles. The abnormal mitotic spindles were resulted from the inactivation of Aurora A by BITC. The fact that BITC inhibits the activation of Aurora A and disrupts mitotic spindles provides one of the possible explanations why BITC is able to arrest cells in the G2/M phase and induce apoptosis in many previous studies. Besides, Aurora A is an essential player of mitosis and also has non-mitotic functions in tumorigenesis. As an inhibitor of Aurora A, BITC not only is an antimitotic agent but also inhibits tumor progression via many pathways.